PENGEMBANGAN PERANGKAT PEMBELAJARAN TEKS PROSEDURAL KOMPLEKS DENGAN PENDEKATAN SAINTIFIK PADA SISWA KELAS X SMA - Ani, Sari (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
This research focuses on developing common learning device by using scientific learning methods, while the focus in particular is a process of development and the quality of learning tools include validity, practicality, and effectiveness. This type of development research using model Four D that includes: 1) define; 2) design 3) develop 4) disseminate The research data is grouped into qualitative and quantitative data. The data collected by observation, questionnaires, and interviews. The results of the study are categorized very valid with details of the percentage of the syllabus (90%), assessment (92%), RPP (90%), and books students (88%), practicality is very practical in terms of the analysis results RPP with a score (98%), student responses with a score (93%), the response of teachers with a score (97%), the effectiveness categorized as very effective in terms of the analysis of the results of the activity of students with scores (92%), observation of activities with a score (99%), and student learning outcomes can be reached completeness with a score (98%).